Pigeons integrate past knowledge across sensory modalities - Stephan, Claudia; Bugnyar, Thomas (Animal Behaviour, 2013)
Advanced inferring abilities that are used for predator recognition and avoidance have been documented in a variety of animal species that produce alarm calls. In contrast, evidence for cognitive abilities that underpin predation avoidance in nonalarm-calling species is restricted to associative learning of heterospecific alarm calls and predator presence. We investigated cognitive capacities that underlie the perception and computation of external information beyond associative learning by addressing contextual information processing in pigeons, Columba livia, a bird species without specific alarm calls. We used a habituation/dishabituation paradigm across sensory modes to test pigeons' context-dependent inferring abilities. The birds reliably took previous knowledge about predator presence into account and responded with predator-specific scanning behaviour only if predator presence was not indicated before or if the perceived level of urgency increased. Hence, pigeons' antipredator behaviour was not based on the physical properties of displayed stimuli or their referential content alone but on contextual information, indicated by the kind and order of stimulus presentation and different sensory modes.<br
Keywords: Columba livia; contextual understanding; cross-modal recognition; pigeon; predator recognition; response urgency